Genome-Wide Analysis of Transposon Insertion Polymorphisms Reveals Intraspecific Variation in Cultivated Rice - Huang, Xuehui (American Society of Plant Biologists, 2008)
Insertions and precise eliminations of transposable elements generated numerous transposon insertion polymorphisms (TIPs) in rice (Oryza sativa). We observed that TIPs represent more than 50% of large insertions and deletions (>100 bp) in the rice genome. Using a comparative genomic approach, we identified 2,041 TIPs between the genomes of two cultivars, japonica Nipponbare and indica 93-11. We also identified 691 TIPs between Nipponbare and indica Guangluai 4 in the 23-Mb collinear regions of chromosome 4. Among them, retrotransposon-based insertion polymorphisms were used to reveal the evolutionary relationships of these three cultivars. Our conservative estimates suggest that the TIPs generated approximately 14% of the genomic DNA sequence differences between subspecies indica and japonica. It was also found that more than 10% of TIPs were located in expressed gene regions, representing an important source of genetic variation. Transcript evidence implies that these TIPs induced a series of genetic differences between two subspecies, including interrupting host genes, creating different expression forms, drastically changing intron length, and affecting expression levels of adjacent genes. These analyses provide genome-wide insights into evolutionary history and genetic variation of rice.